ضوابط التفتيش وآثاره في الفقه الإسلامي والقانون الجزائري تفتيش الأشخاص والمساكن "انموذجا - قريرة, هنـــاء (University of eloued جامعة الوادي, 2016)
إن التفتيش هو البحث عن الدليل بالنسبة للجريمة، ويتمثل في الاطّلاع على محل ما منح له القانون حرمة خاصة لغاية أساسية قدرها المشرع وهي الكشف عن حقيقة جريمة قد وقعت، حيث يعتبر إجراء التفتيش من إجراءات التحقيق الابتدائي سواء كان بالنسبة للأشخاص أو المساكن، والذي فيه مساس بالحريات التي تكفلت بها كل من الشريعة الإسلامية والقانون، وعليه خولت سلطة مباشرة هذا الإجراء إلى سلطة التحقيق ويعقد استثناءا إلى ضابط الشرطة القضائية، وهذا ملخص ما تطرقتُ إليه في المبحث التمهيدي، وبما أن التفتيش فيه مساس بالحريات الشخصية، فقد أحاطه المشرع بضمانات عديدة ووضع له ضوابط وأحكام معينة والتي تطرقْتُ إليها في الفصل الأول، وتحت طائلة البطلان فلا يجوز للنيابة العامة مباشرة هذا الإجراء بغير إذن من السلطة المختصة إلا في أحوال استثنائية حددها القانون وتتمثل في حالة الجرم المشهود )التلبس- القبض( وفي حالة الدخول بناءا على طلب من صاحب المنزل، حيث أن بطلان التفتيش لا يعني براءة المتهم، بل استبعاد الأدلة المستمدة وعدم الاعتداد بها في الإثبات، أما من حيث الآثار فإن الضبط هو الأثر المباشر للتفتيش ولا بد أن ينصب على الأشياء التي تفيد في كشف الحقيقة وهذا ما تطرقت إليه في الفصل الثاني.The inspection is to look for evidence for the crime, and is looking at their place of granting him the law, particularly the sanctity of basic highly of the legislature, a disclosure of the fact that a crime has occurred, where is the action of the procedures of primary investigations, whether it was for people or houses, which touches the personal freedom guaranteed by both Islamic law and the Constitution, which empowered the authority to direct this procedure to the authority to investigate and hold an exception to the judicial police officer, and that's what touched in section introductory summary, and as the inspection is prejudicial to personal freedom it has been surrounded with several guarantees by the legislator and put his controls and certain terms, which I touched upon in the first chapter, and under the objection of this procedure, it is not permitted to the public prosecution to do so without competent authority's permission , but in exceptional circumstances which are defined by law example in the case of witnessed misdeed or crime (flagrant crime- arrest) in the case of entry of any house depending on the request of the owner, so the invalidity of inspections does not mean that the innocence of the accused, but it means the exclusion or the neglection of derived evidence and don't depend on them in proofing , and concerning the terms of traces, the setting is the direct impact on the inspections it must be focussed on the things that can benefit in revealing the truth and that's what we have touched in the second chapter
شريعة و قانون
Keywords: التفتيش/الفقه الإسلامي/المساكن; Inspection / Islamic jurisprudence / housing